Ilmu Kantong Bolong R.M.P Sosrokartono Dalam Perspektif Moralitas Dan Implementasinya Pada Kehidupan Milenial - Ahmad Miftahudin Thohari; Lia Faridatun Nisa; Nur Azizah; Rina Mutoharoh; Erdiana Aris Tantia (Academica : Journal of Multidisciplinary Studies, 2022)
Ilmu Kantong Bolong was one of the ideas propounded by R.M.P sosrokartono. It is the teaching that gives understanding to man that in life all the material riches that a man has should not be kept in tight order, but should always be directed to his fellowmen who need them. Wealth does not belong to absolute humans but only to those in need. Through literature studies (library research), it has been produced that in a moral perspective the doctrine of Ilmu Kantong Bolong contained the doctrine of humanity. It is that people should help one another and give to one another. So in its implementation of life today, successive generations can apply that moral teaching so as not to choose to be selfish and individualistic only for themselves. Keywords: Ilmu Kantong Bolong; Sosrokartono; Morality, Milenials Generation